2017
DOI: 10.18632/oncotarget.20349
|View full text |Cite
|
Sign up to set email alerts
|

The effect ofMVK-MMABvariants, their haplotypes and G×E interactions on serum lipid levels and the risk of coronary heart disease and ischemic stroke

Abstract: AimThis study aimed to detect the association of the mevalonate kinase (MVK) and methylmalonic aciduria (cobalamin deficiency) cblB type (MMAB) gene variants, their haplotypes, and gene-environment (G×E) interactions on serum lipid levels and the risk of coronary heart disease (CHD) and ischemic stroke (IS) in a Chinese Han population.MethodsGenotyping of the rs3759387, rs7134594, rs877710 and rs9593 SNPs in 846 CHD and 869 IS patients and 847 healthy controls was performed by PCR-RFLP and Sanger sequencing. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 64 publications
(47 reference statements)
1
21
0
Order By: Relevance
“…Mutations in the MVK gave rise to hyperimmunoglobulinemia D syndrome (HIDS), in which low HDL-C levels could be found (16), in accordance with the latest GWAS findings (12,13). Several novel loci in MVK were confirmed to be associated with serum HDL-C levels (17)(18)(19) and an increased risk of CHD and IS (19). But no significant association between the MVK rs2287218 SNP and serum lipid levels was conducted by Sun et al in a Northern Chinese Han population (20).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Mutations in the MVK gave rise to hyperimmunoglobulinemia D syndrome (HIDS), in which low HDL-C levels could be found (16), in accordance with the latest GWAS findings (12,13). Several novel loci in MVK were confirmed to be associated with serum HDL-C levels (17)(18)(19) and an increased risk of CHD and IS (19). But no significant association between the MVK rs2287218 SNP and serum lipid levels was conducted by Sun et al in a Northern Chinese Han population (20).…”
Section: Discussionsupporting
confidence: 69%
“…The subjects with CT/TT genotypes of the MVK rs2287218 SNP contributed to the increased risk of CHD and IS. A previous study confirmed that the MVK rs3759387 AC/CC genotypes interacted with some environmental exposures (such as males, elder), resulting in increasing the risk of CHD and IS (19), which suggested gene-environment interactions contributed to higher risk of CHD and IS. It was reported that the MVK variants displayed low HDL-C levels and an activity decline of the MVK.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Currently, the diagnosis of CAD is based on ischaemiarelated symptoms, detailed physical examination, electrocardiogram changes, elevated biomarkers of myocardial injury and coronary angiography [32,33]. Meanwhile, the diagnosis of ischaemic stroke (IS) is also based on the patient's symptoms, signs, strict neurological examination SBP Systolic blood pressure, DBP Diastolic blood pressure, PP Pulse pressure, Glu Glucose, HDL-C high-density lipoprotein cholesterol, LDL-C low-density lipoprotein cholesterol, Apo Apolipoprotein, TC Total cholesterol, TG Triglyceride a Continuous data were presented as means ± SD and determined by two side t-test b A chi-square analysis was used to evaluate the difference of the rate between the groups and MRI scans [34]. However, the early diagnosis of CAD and IS is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…The blood samples were collected before PCI and just a few hours after chest pain occurred, and were very suitable for the development of early diagnosis biomarkers. Clinical data collection, biochemical measurements and diagnostic criteria were performed according to previous studies [27,28]. The Declaration of Helsinki of 1975 (http:// www.wma.net/en/30publications/10policies/b3/), which was revised in 2008, was followed, and the Ethics Committee of Liuzhou people's Hospital agreed with the study design (No: Lunshen-2017-KY; Mar.…”
Section: Study Populationmentioning
confidence: 99%